The Influence of Corporate Governance on The Quality of Financial Reports In Banking Companies Listed on The Indonesia Stock Exchange (IDX) For The Period 2021-2024 - Imelda Fisianca Lubis; Halomoan S. Sihombing; Mei Hotma Mariati Munte (Indonesian Journal Economic Review (IJER), 2026)
This study aims to analyze the effect of Corporate Governance proxied by Transparency, Accountability, and Independence-on Financial Statement Quality. In this study, financial statement quality is measured using timeliness. Meanwhile, the proxies for the independent variables include Transparency, measured by the disclosure index; Accountability, measured by the frequency of audit committee meetings; and Independence, measured by the proportion of inindependent commissioners. The population for this study consists of alla banking companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2024 period. Sampling was conducted using purposive sampling, resulting in 22 banking companies that met the study criteria. The data analysis technique used was panel data regression analysis with the assistance of EViews software. The results show that Accountability has a positive and significant effect on Financial Statement Quality, while Transparency and Independence do not have a significant effect on Financial Statement Quality.